Assessment of SARS-CoV-2 infectivity of upper respiratory specimens from COVID-19 patients by virus isolation using VeroE6/TMPRSS2 cells. Issue 1 (24th February 2021) - Yamada, Souichi; Fukushi, Shuetsu; Kinoshita, Hitomi; Ohnishi, Makoto; Suzuki, Tadaki; Fujimoto, Tsuguto; Saijo, Masayuki; Maeda, Ken
Abstract : Background: An outbreak of novel coronavirus (SARS-CoV-2)-associated respiratory infectious diseases (COVID-19) emerged in 2019 and has spread rapidly in humans around the world. The demonstration of in vitro infectiousness of respiratory specimens is an informative surrogate for SARS-CoV-2 transmission from patients with COVID-19; accordingly, viral isolation assays in cell culture are an important aspect of laboratory diagnostics for COVID-19. Methods: We developed a simple and rapid protocol for isolating SARS-CoV-2 from respiratory specimens using VeroE6/TMPRSS2 cells, a cell line that is highly susceptible to the virus. We also investigated a correlation between isolation of SARS-CoV-2 and viral load detected by real-time RT-PCR (rRT-PCR) using N2 primer/probe set that has been developed for testing of COVID-19 in Japan. Results: The SARS-CoV-2 isolation protocol did not require blind passage of inoculated cells and yielded the results of viral isolation within 7 days after inoculation. Specimens with cycle threshold (Ct) values of <20.2, determined by rRT-PCR, were predicted to be isolation-positive. On the other hand, 6.9% of specimens with Ct values >35 were virus isolation-positive, indicating that low viral loads (high Ct values) in upper respiratory specimens do not always indicate no risk of containing transmissible virus. Conclusion: In combination with rRT-PCR, the SARS-CoV-2 isolation protocol provides a means for assessing the potential risk of transmissible virus in upper respiratory specimens.